Three-dimensional dynamics of functionally graded piezoelectric cylindrical panels by a semi-analytical approach. (15th October 2019) - Liang, Xu; Deng, Yu; Cao, Zeng; Jiang, Xue; Wang, Titao; Ruan, Yongdu; Zha, Xing
Abstract: Nowadays, intelligent piezoelectric materials are widely used in transducer devices and aerospace structures. To investigate the dynamic behaviour of a functionally graded piezoelectric material (FGPM) cylindrical panel, a semi-analytical approach by introducing the Laplace transform, differential quadrature method, state space approach and Durbin's numerical inversion of Laplace transform is presented. The accuracy of this method is validated by comparing the results with the published literature and by ANSYS under various boundary conditions. Convergence studies showed the proposed approach has a quick convergence rate with growing sample point numbers and increasing layer numbers. The analysis of initial electric potential on the outer surface and bottom surface indicated that when the plus and minus signs of two sides are opposite, the value of central electric potential will decrease. Under simply supported condition, if FG index γ increases, the deflection amplitude of the panel will increase, while the electric potential amplitude decreases. Moreover, the amplitude of displacements along the radial direction becomes larger when the central angle increases, but the period time decreases at the same time. The proposed method fills a gap of 3-D semi-analytical investigations for the dynamic behaviour of FGPM cylindrical panels in different boundary conditions.